2022
DOI: 10.1039/d1na00743b
|View full text |Cite
|
Sign up to set email alerts
|

Utilising problematic waste to detect toxic gas release in the environment: fabricating a NiO doped CuO nanoflake based ammonia sensor from e-waste

Abstract: Using problematic electronic waste to synthesise high-purity nanomaterials can enable sustainable production and create opportunities to divert waste from landfills. Current research represents a facile strategy for the controllable synthesis...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 70 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…ME and CA phases were simultaneously identified based on the Rietveld refinement process and this phase refinement gives a better phase match between observed patterns and reference patterns. The diffraction peak's width and shape were fit to functions that describe their systematic behavior connected to 2 θ (Hossain et al., 2022). The 2 θ peak position and intensity of diffraction peaks are assessed from the crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…ME and CA phases were simultaneously identified based on the Rietveld refinement process and this phase refinement gives a better phase match between observed patterns and reference patterns. The diffraction peak's width and shape were fit to functions that describe their systematic behavior connected to 2 θ (Hossain et al., 2022). The 2 θ peak position and intensity of diffraction peaks are assessed from the crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…The sensor showed a response of 0.6 towards 200 ppm NH 3 at a RT of 20 °C. 17 Haunsbhavi et al reported a NiO thin film based NH 3 sensor, synthesized by the sol-gel spin coating technique. This sensor revealed an acceptable response towards 5 ppm NH 3 at an operating temperature of 150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, researchers have investigated various types of metal oxides, such as CuO [ 22 , 23 ], MnO 2 [ 24 ], NiO [ 25 ], Fe 2 O 3 [ 26 ], and ZnO [ 27 ], as electron mediators for sensing applications. Additionally, doped metal oxides, such as NiO.CoO nanocomposites [ 28 ], CdO.SnO 2 .V 2 O 5 [ 29 ], CuO.In 2 O 3 [ 30 ], CuO.Nd 2 O 5 [ 31 ], CuO.NiO [ 32 ], and CuO.ZnO [ 33 ], have been studied as efficient sensing materials with higher sensitivity, small detection limits, wide linear dynamic ranges, and quick response times. CuO, a p -type semiconductor, has shown particularly good performance as an electrocatalyst in sensing applications [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…CuO, a p -type semiconductor, has shown particularly good performance as an electrocatalyst in sensing applications [ 34 ]. To improve the performance of CuO, researchers have also investigated using other semiconductor metal oxides such as In 2 O 3 [ 30 ], Nd 2 O 5 [ 31 ], NiO [ 32 ], TiO 2 [ 35 ], and SnO 2 [ 36 ] in combination with CuO as bimetallic oxide pairs. Ytterbium oxide (Yb 2 O 3 ) has also been explored for use in sensing applications [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%